Optimization of Job Training in Improving Yantek Performance at PT XYZ With ADDIE Model Design - Aneke Putri Nadila; Hafid Syaifullah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Job training is the key to improving the performance of Technical Service Officers (Yantek) at PT XYZ.. This study aims to evaluate the effectiveness of ongoing job training and identify areas that need improvement. Through an in-depth analysis of the training curriculum, teaching methods, and Yantek performance after training, this study proposes recommendations for optimizing the training program. The results of the study are expected to improve the quality of service to customers and support the achievement of company performance targets.